Effect of pH on the adsorption of methyl orange using base modified activated carbon-based on oil palm fronds - Taib, Nurul Izza; Erul Farhan, Ezaril Harith; Yasmin, Nurin Jesnita; Shamsul, Nur Iman Aisya; Sulaiman, Syukrina; Abdullah, Nurul Ellyana; Hishamliza, Irfan Shah; Addysuriono, Adlyn Suraya; Md Nizam, Aina Maisarah (2024)
The present study has developed an eco-friendly method for green synthesis of base-modified activated carbon (NaOHAC) based on oil palm fronds. By utilizing a waste product from the oil palm industry, this approach not only addresses the issue of waste management but also contributes to environmental sustainability. The percentage of methyl orange removed was determined by monitoring the changes in its concentration using UVVis spectrophotometry as pH varied. The methyl orange of 50 ppm is almost completely removed at pH 2.0 within 1 hour of the reaction. The findings suggest that NaOHAC, which produced from a waste material, has a high potential as an adsorbent for removing dyes from water.